Deposition of metal particles onto semiconductor nanorods using an ionic liquid - Ballentine, Michael D.; Embry, Elizabeth G.; Garcia, Marco A.; Hill, Lawrence J. (Beilstein Journal of Nanotechnology, 2019)
The current study investigates whether metal deposition onto an existing nanorod can be carried out using an ionic liquid, and the effect this has on catalytic performance. Platinum, gold, and silver nanoparticles were deposited onto CdSe@CdS (core@shell) nanorods from metal salts in an ionic liquid (1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) without additional surfactants or reducing agents. Photocatalytic dye degradation experiments showed that catalysts with platinum particles deposited using the ionic liquid out-performed similar materials synthesized using organic solvents and ligands. We concluded that metal particles can be deposited onto well-defined semiconductor nanorods using ionic liquids and metal salts without the need for additional reagents, and the deposited particles did not cause significant aggregation even when these materials were taken into organic media. It is possible that a broad range of metal/semiconductor heterostructured particles can be prepared using the methods reported here.
Keywords: catalyst; ionic liquid; methylene blue; platinum; semiconductor nanorod

(untitled) - Banin, U.; Ben-Shahar, Y.; Vinokurov, K. (Chem. Mater., 2014)

(untitled) - Buck, M. R.; Schaak, R. E. (Angew. Chem., Int. Ed., 2013)

(untitled) - Sitt, A.; Hadar, I.; Banin, U. (Nano Today, 2013)

(untitled) - Kamat, P. V. (J. Phys. Chem. Lett., 2012)

(untitled) - Sun, Y. (Natl. Sci. Rev., 2015)

(untitled) - Puzder, A.; Williamson, A. J.; Zaitseva, N.; Galli, G.; Manna, L.; Alivisatos, A. P. (Nano Lett., 2004)

(untitled) - Lee, S.; Wang, Y.; Liu, Y.; Lee, D.; Lee, K.; Lee, D. C.; Lian, T. (Chem. Phys. Lett., 2017)

(untitled) - Ben-Shahar, Y.; Scotognella, F.; Waiskopf, N.; Kriegel, I.; Dal Conte, S.; Cerullo, G.; Banin, U. (Small, 2015)

(untitled) - Tarafder, K.; Surendranath, Y.; Olshansky, J. H.; Alivisatos, A. P.; Wang, L.-W. (J. Am. Chem. Soc., 2014)

(untitled) - Khon, E.; Lambright, K.; Khnayzer, R. S.; Moroz, P.; Perera, D.; Butaeva, E.; Lambright, S.; Castellano, F. N.; Zamkov, M. (Nano Lett., 2013)

(untitled) - O’Connor, T.; Panov, M. S.; Mereshchenko, A.; Tarnovsky, A. N.; Lorek, R.; Perera, D.; Diederich, G.; Lambright, S.; Moroz, P.; Zamkov, M. (ACS Nano, 2012)

(untitled) - Kim, J.-Y.; Kotov, N. A. (Chem. Mater., 2014)

(untitled) - Wegner, S.; Janiak, C. (Top. Curr. Chem., 2017)

(untitled) - Dupont, J. (J. Braz. Chem. Soc., 2004)

(untitled) - Dupont, J.; Scholten, J. D. (Chem. Soc. Rev., 2010)

(untitled) - Vollmer, C.; Janiak, C. (Coord. Chem. Rev., 2011)

(untitled) - Antonietti, M.; Kuang, D.; Smarsly, B.; Zhou, Y. (Angew. Chem., Int. Ed., 2004)

(untitled) - Esteban, R. M.; Schütte, K.; Brandt, P.; Marquardt, D.; Meyer, H.; Beckert, F.; Mülhaupt, R.; Kölling, H.; Janiak, C. (Nano-Struct. Nano-Objects, 2015)

(untitled) - Marquardt, D.; Beckert, F.; Pennetreau, F.; Tölle, F.; Mülhaupt, R.; Riant, O.; Hermans, S.; Barthel, J.; Janiak, C. (Carbon, 2014)

(untitled) - Janiak, C. (Z. Naturforsch., B: J. Chem. Sci., 2013)

(untitled) - Marquardt, D.; Vollmer, C.; Thomann, R.; Steurer, P.; Mülhaupt, R.; Redel, E.; Janiak, C. (Carbon, 2011)

(untitled) - Li, F.; Yang, H.; Shan, C.; Zhang, Q.; Han, D.; Ivaska, A.; Niu, L. (J. Mater. Chem., 2009)

(untitled) - Wang, Z.; Zhang, Q.; Kuehner, D.; Xu, X.; Ivaska, A.; Niu, L. (Carbon, 2008)

(untitled) - Chun, Y. S.; Shin, J. Y.; Song, C. E.; Lee, S.-g. (Chem. Commun., 2008)

(untitled) - Biswas, K.; Rao, C. N. R. (Chem. – Eur. J., 2007)

(untitled) - Ben-Shahar, Y.; Banin, U. (Top. Curr. Chem., 2016)

(untitled) - Hill, L. J.; Bull, M. M.; Sung, Y.; Simmonds, A. G.; Dirlam, P. T.; Richey, N. E.; DeRosa, S. E.; Shim, I.-B.; Guin, D.; Costanzo, P. J.; Pinna, N.; Willinger, M.-G.; et al. (ACS Nano, 2012)

(untitled) - Carbone, L.; Nobile, C.; De Giorgi, M.; Sala, F. D.; Morello, G.; Pompa, P.; Hytch, M.; Snoeck, E.; Fiore, A.; Franchini, I. R.; Nadasan, M.; Silvestre, A. F.; et al. (Nano Lett., 2007)

(untitled) - Yu, W. W.; Qu, L.; Guo, W.; Peng, X. (Chem. Mater., 2003)

(untitled) - Dukovic, G.; Merkle, M. G.; Nelson, J. H.; Hughes, S. M.; Alivisatos, A. P. (Adv. Mater. (Weinheim, Ger.), 2008)

(untitled) - Wang, Y.; Yang, H. (J. Am. Chem. Soc., 2005)

(untitled) - Prechtl, M. H. G.; Scholten, J. D.; Dupont, J. (Molecules, 2010)

(untitled) - Deshmukh, R. R.; Rajagopal, R.; Srinivasan, K. V. (Chem. Commun., 2001)

(untitled) - Li, Z.; Friedrich, A.; Taubert, A. (J. Mater. Chem., 2008)

(untitled) - Nakibli, Y.; Kalisman, P.; Amirav, L. (J. Phys. Chem. Lett., 2015)

(untitled) - Amirav, L.; Alivisatos, A. P. (J. Phys. Chem. Lett., 2010)

(untitled) - Wand, P.; Bartl, J. D.; Heiz, U.; Tschurl, M.; Cokoja, M. (J. Colloid Interface Sci., 2016)

(untitled) - Wu, K.; Chen, Z.; Lv, H.; Zhu, H.; Hill, C. L.; Lian, T. (J. Am. Chem. Soc., 2014)

(untitled) - Menagen, G.; Mocatta, D.; Salant, A.; Popov, I.; Dorfs, D.; Banin, U. (Chem. Mater., 2008)

(untitled) - Saunders, A. E.; Popov, I.; Banin, U. (J. Phys. Chem. B, 2006)